Grinding method

By employing a polishing liquid composition with silica particles and an amino group-containing polymer, the polishing rate and surface quality of silicon substrates are enhanced, addressing the inefficiencies of existing compositions and improving semiconductor manufacturing processes.

JP7606315B2Active Publication Date: 2024-12-25KAO CORP
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2020171486
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-09
Publication Date
2024-12-25
Estimated Expiration
2040-10-09

AI Technical Summary

Technical Problem

Existing polishing liquid compositions for silicon substrates, particularly in final polishing stages, suffer from insufficient polishing rates and surface defects, which are exacerbated by the use of colloidal silica with smaller particle sizes that slow down the process.

Method used

A polishing method using a composition containing silica particles with a negative zeta potential and an amino group-containing water-soluble polymer, where the zeta potential of the silicon substrate is adjusted to be positive, enhancing the attractive force and contact frequency between the silica particles and the substrate to improve polishing efficiency.

Benefits of technology

The method significantly improves the polishing rate and reduces surface defects, achieving higher quality and productivity in semiconductor substrate manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606315000001
    Figure 0007606315000001
  • Figure 0007606315000002
    Figure 0007606315000002
  • Figure 0007606315000003
    Figure 0007606315000003
Patent Text Reader

Abstract

To provide, in one aspect, a polishing method for a silicon substrate which can increase the polishing speed.SOLUTION: In one aspect, a polishing method comprises polishing a to-be-polished silicon substrate using a polishing liquid composition containing silica particles (component A) and an amino group-containing water-soluble polymer (component B), where the polishing is performed under conditions that the zeta potential of the component A should be negative and the zeta potential of the to-be-polished silicon substrate should be positive.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for polishing a silicon substrate and a method for manufacturing a semiconductor substrate. [Background technology]

[0002] In recent years, the demand for higher storage capacity of semiconductor memory has led to the trend toward finer design rules for semiconductor devices. As a result, the depth of focus in photolithography used in the manufacturing process of semiconductor devices has become shallower, and the demands for reduced defects and smoothness of silicon substrates (bare wafers) have become increasingly strict.

[0003] To improve the quality of silicon substrates, polishing of silicon substrates is carried out in multiple stages. In particular, the final polishing stage is carried out to suppress surface roughness (haze) and to suppress surface defects (LPD: Light point defects) such as particles, scratches, and pits by improving the wettability (hydrophilicity) of the silicon substrate surface after polishing.

[0004] The allowable size of surface defects on silicon substrate surfaces is getting smaller every year, and these defects are usually measured by irradiating the substrate surface with laser light and detecting the scattered light. Therefore, in order to measure smaller defects, it is necessary to reduce the surface roughness (haze) of the silicon substrate and improve the S / N ratio when measuring defects.

[0005] As a polishing composition used in the finish polishing, a polishing composition for chemical mechanical polishing using colloidal silica and an alkaline compound is known (Patent Documents 1 to 3).

[0006] Patent Document 1 reports a polishing composition containing a water-soluble polymer compound such as hydroxyethyl cellulose or polyethylene oxide as a polishing composition intended to improve the haze level. Patent Document 2 reports a polishing composition containing a water-soluble polymeric compound having a nitrogen-containing group, such as polyvinylpyrrolidone and poly-N-vinylformamide, as a polishing composition intended to reduce the number of surface defects (LPD). Patent Document 3 reports a polishing liquid containing a water-soluble polymeric compound having a nitrogen-containing group, such as polyethyleneimine, as a polishing liquid composition that aims to simultaneously achieve a high polishing rate and prevent surface roughening of the substrate after polishing. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2004-128089 A [Patent Document 2] JP 2008-53415 A [Patent Document 3] JP 2007-19093 A Summary of the Invention [Problem to be solved by the invention]

[0008] In order to reduce surface defects, colloidal silica with smaller particle size is used in the polishing liquid used in the finish polishing, but the polishing speed tends to be slower, and there is a problem in improving the polishing speed. However, in polishing using the polishing compositions of Patent Documents 1 to 3, the removal rate is not sufficient.

[0009] The present disclosure provides a method for polishing a silicon substrate and a method for manufacturing a semiconductor substrate, which can improve the polishing rate. [Means for solving the problem]

[0010] In one embodiment, the present disclosure includes a step of polishing a silicon substrate using a polishing composition containing silica particles (component A) and an amino group-containing water-soluble polymer (component B), The polishing method is carried out under the condition that the zeta potential of component A is negative and the zeta potential of the silicon substrate to be polished is positive.

[0011] In one aspect, the present disclosure relates to a method for producing a semiconductor substrate, the method including the steps of polishing a silicon substrate to be polished using the polishing method of the present disclosure, and cleaning the polished silicon substrate. Effect of the Invention

[0012] According to the present disclosure, it is possible to provide a method for polishing a silicon substrate and a method for manufacturing a semiconductor substrate, which are capable of improving the polishing rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present disclosure is based on the finding that a silicon substrate can be polished at high speed by using a polishing composition containing silica particles and an amino group-containing water-soluble polymer under conditions where the zeta potential of the silica particles is negative and the zeta potential of the silicon substrate to be polished is positive.

[0014] That is, in one aspect, the present disclosure relates to a polishing method (hereinafter also referred to as the "polishing method of the present disclosure") that includes a step of polishing a silicon substrate to be polished with a polishing liquid composition containing silica particles (component A) and an amino group-containing water-soluble polymer (component B), and the polishing is performed under conditions where the zeta potential of component A is negative and the zeta potential of the silicon substrate to be polished is positive.

[0015] According to the present disclosure, in one or more embodiments, the removal rate can be improved.

[0016] Although the details of the mechanism by which the effects of the present disclosure are exerted are not clear, it is presumed as follows. Because the zeta potential of the abrasive particles, silica particles (component A), and the zeta potential of the silicon substrate being polished have opposite signs, an attractive force acts between the silica particles (component A) and the silicon substrate being polished, increasing the force acting on and / or the number of contacts between the silica particles (component A) and the silicon substrate being polished, and as a result, it is believed that the polishing rate is improved. The zeta potential of the silica particles (component A) and the zeta potential of the silicon substrate to be polished are generally both negative, but in the present disclosure, it is believed that it is possible to improve the polishing rate by adsorbing an amino group-containing water-soluble polymer compound (component B) to the silica particles (component A) or the silicon substrate to be polished, keeping the zeta potential of the silica particles (component A) negative and adjusting the zeta potential of the silicon substrate to be polished positive. However, the present disclosure need not be construed as being limited to these mechanisms.

[0017] [Polishing process] The polishing method of the present disclosure includes a step of polishing a silicon substrate to be polished (hereinafter also referred to as the "polishing step of the present disclosure") using a polishing liquid composition containing silica particles (component A) and an amino group-containing water-soluble polymer (component B) (hereinafter also referred to as the "polishing liquid composition of the present disclosure"). The polishing in the polishing step of the present disclosure is performed under conditions where the zeta potential of component A is negative and the zeta potential of the silicon substrate to be polished is positive.

[0018] The zeta potential of component A is usually negative, and in the polishing step of the present disclosure, the zeta potential of component A remains negative even if component B is adsorbed to component A. In the polishing step of the present disclosure, the zeta potential of component A in the polishing liquid composition of the present disclosure is preferably -50 mV or more, more preferably -45 mV or more, even more preferably -40 mV or more, and even more preferably -35 mV or more, from the viewpoint of reducing surface roughness and surface defects, and is preferably less than 0 mV, more preferably -10 mV or less, even more preferably -15 mV or less, even more preferably -20 mV or less, and even more preferably -25 mV or less, from the viewpoint of improving the polishing rate.

[0019] The zeta potential of the silicon substrate to be polished is usually negative, but in the polishing process of the present disclosure, the zeta potential of the silicon substrate to be polished becomes positive by adsorbing component B to the silicon substrate to be polished. In the polishing process of the present disclosure, the zeta potential of the silicon substrate to be polished is preferably more than 0 mV, more preferably +1 mV or more, even more preferably +2 mV or more, and even more preferably +3 mV or more, from the viewpoint of improving the polishing rate, and is preferably +30 mV or less, more preferably +25 mV or less, even more preferably +20 mV or less, even more preferably +15 mV or less, even more preferably +10 mV or less, and even more preferably +9 mV or less, from the viewpoint of surface cleanliness due to residual silica particles on the surface.

[0020] In the polishing process of the present disclosure, the difference between the zeta potential of the silicon substrate to be polished and the zeta potential of the silica particles (component A) is preferably 10 mV or more, more preferably 20 mV or more, and even more preferably 25 mV or more, from the viewpoint of improving the polishing rate, and is preferably 60 mV or less, more preferably 50 mV or less, and even more preferably 45 mV or less, from the viewpoint of facilitating adjustment of the zeta potential.

[0021] In the polishing step of the polishing method of the present disclosure, for example, the silicon substrate can be pressed against a platen to which a polishing pad is attached, and the silicon substrate can be polished at a polishing pressure of 3 to 20 kPa. In the present disclosure, the polishing pressure refers to the pressure of the platen applied to the surface of the silicon substrate during polishing.

[0022] In the polishing step of the polishing method of the present disclosure, for example, a silicon substrate to be polished can be pressed against a platen to which a polishing pad is attached, and the silicon substrate to be polished can be polished with a polishing liquid composition and a polishing pad surface temperature of 15° C. to 40° C. From the viewpoint of achieving both an improvement in the polishing rate and surface quality such as a reduction in surface roughness (haze), the temperature of the polishing liquid composition and the polishing pad surface temperature are preferably 15° C. or higher or 20° C. or higher, and preferably 40° C. or lower or 30° C. or lower.

[0023] [Polished silicon substrate] The polishing method of the present disclosure is a method for polishing a silicon substrate, and can be used, for example, in a polishing step of polishing a silicon substrate to be polished in a method for manufacturing a semiconductor substrate, or in a polishing step of polishing a silicon substrate to be polished in a method for polishing a silicon substrate. In one or more embodiments, the silicon substrate to be polished using the polishing liquid composition of the present disclosure can be a silicon substrate, etc., and in one or more embodiments, a single crystal silicon substrate, a polysilicon substrate, a substrate having a polysilicon film, a SiN substrate, etc. can be used. From the viewpoint of exerting the effect of the polishing liquid composition of the present disclosure, a single crystal silicon substrate or a polysilicon substrate is preferred, and a single crystal silicon substrate is more preferred.

[0024] [Silica particles (component A)] The polishing liquid composition of the present disclosure contains silica particles (hereinafter also referred to as "Component A") as an abrasive. Component A includes colloidal silica, fumed silica, pulverized silica, and surface-modified silica thereof, and from the viewpoint of achieving both improved polishing rate and storage stability, and from the viewpoint of improving surface quality such as reducing surface roughness (haze), surface defects, and scratches, colloidal silica is preferred. Component A may be one type or a combination of two or more types.

[0025] From the viewpoint of operability, the use form of component A is preferably a slurry form.When component A contained in the polishing liquid composition of the present disclosure is colloidal silica, from the viewpoint of preventing contamination of silicon substrate by alkali metal, alkaline earth metal, etc., the colloidal silica is preferably obtained from the hydrolysis product of alkoxysilane.The silica particles obtained from the hydrolysis product of alkoxysilane can be produced by a conventionally known method.

[0026] From the viewpoint of maintaining the polishing rate, the average primary particle diameter of component A is preferably 10 nm or more, more preferably 20 nm or more, and from the viewpoint of improving storage stability and improving surface quality such as reducing surface roughness (haze), surface defects and scratches, it is preferably 50 nm or less, more preferably 45 nm or less, even more preferably 40 nm or less, and even more preferably 30 nm or less. From the same viewpoint, the average primary particle diameter of component A is preferably 10 nm or more and 50 nm or less, more preferably 20 nm or more and 45 nm or less, even more preferably 20 nm or more and 40 nm or less, and preferably 20 nm or more and 30 nm or less. In the present disclosure, the average primary particle size of component A is determined by the specific surface area S (m 2 The average primary particle size is calculated using the formula (1 / g). The average primary particle size is a value measured by the method described in the Examples.

[0027] From the viewpoint of maintaining the polishing rate, the average secondary particle diameter of component A is preferably 20 nm or more, more preferably 30 nm or more, and even more preferably 40 nm or more, and from the viewpoint of improving storage stability and improving surface quality such as reducing surface roughness (haze), surface defects and scratches, it is preferably 100 nm or less, more preferably 90 nm or less, even more preferably 80 nm or less, even more preferably 70 nm or less, and even more preferably 60 nm or less. From the same viewpoint, the average secondary particle diameter of component A is preferably 20 nm or more and 100 nm or less, more preferably 30 nm or more and 90 nm or less, even more preferably 30 nm or more and 80 nm or less, even more preferably 30 nm or more and 70 nm or less, and even more preferably 40 nm or more and 60 nm or less. In the present disclosure, the average secondary particle size is a value measured by a dynamic light scattering (DLS) method, and is a value measured by the method described in the Examples.

[0028] From the viewpoints of improving the storage stability and improving the surface quality, the degree of association of component A is preferably 3 or less, more preferably 2.5 or less, and even more preferably 2.3 or less, and from the viewpoints of achieving both an improvement in the removal rate and storage stability, and of improving the surface quality, the degree of association of component A is preferably 1.1 or more, more preferably 1.5 or more, and even more preferably 1.8 or more.

[0029] In the present disclosure, the degree of association of component A is a coefficient representing the shape of the silica particles and is calculated by the following formula. Degree of association = average secondary particle size / average primary particle size

[0030] The degree of association of Component A can be adjusted by using the methods described in, for example, JP-A-6-254383, JP-A-11-214338, JP-A-11-60232, JP-A-2005-060217, JP-A-2005-060219, and the like.

[0031] The shape of component A is preferably a so-called spherical shape and / or a so-called cocoon shape from the viewpoints of achieving both an improvement in removal rate and storage stability, and from the viewpoints of improving surface quality.

[0032] The content of Component A in the polishing composition of the present disclosure is, from the viewpoint of improving the polishing rate, SiO 2 In terms of conversion, the content is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.07% by mass or more, and from the viewpoint of improving storage stability, reducing surface roughness, and reducing residues on the silicon substrate surface, it is preferably 2.5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.8% by mass or less. Therefore, the content of component A in the polishing liquid composition of the present disclosure is preferably 0.01% by mass or more and 2.5% by mass or less, more preferably 0.05% by mass or more and 1% by mass or less, and even more preferably 0.07% by mass or more and 0.8% by mass or less. When component A is a combination of two or more types, the content of component A refers to the total content thereof. Furthermore, when the silicon substrate to be polished is a single crystal silicon substrate, the content of component A in the polishing liquid composition of the present disclosure is more preferably 0.5 mass% or less, more preferably 0.3 mass% or less, and even more preferably 0.2 mass% or less, from the viewpoint of improving storage stability, reducing surface roughness, and reducing residues on the silicon substrate surface. Therefore, the content of component A in the polishing liquid composition of the present disclosure is more preferably 0.07 mass% or more and 0.5 mass% or less, more preferably 0.07 mass% or more and 0.3 mass% or less, and even more preferably 0.07 mass% or more and 0.2 mass% or less. Furthermore, when the silicon substrate to be polished is a polysilicon substrate, the content of component A in the polishing liquid composition of the present disclosure is more preferably 0.1 mass% or more, more preferably 0.2 mass% or more, and even more preferably 0.3 mass% or more, from the viewpoint of improving the polishing rate. Therefore, the content of component A in the polishing liquid composition of the present disclosure is more preferably 0.1 mass% or more and 0.8 mass% or less, even more preferably 0.2 mass% or more and 0.8 mass% or less, and even more preferably 0.3 mass% or more and 0.8 mass% or less.

[0033] [Amino group-containing water-soluble polymer (component B)] The polishing liquid composition of the present disclosure contains an amino group-containing water-soluble polymer (hereinafter also referred to as "Component B"). Component B is considered to be able to adjust the zeta potential of the silica particles (Component A) and the silicon substrate to be polished, reduce the electrostatic repulsion between the silica particles (Component A) and the silicon substrate to be polished, and suppress the aggregation of the silica particles. In the present disclosure, "water-soluble" means having a solubility of 0.5 g / 100 mL or more in water (20°C), preferably 2 g / 100 mL or more.

[0034] The pKa of component B is preferably greater than 6.7, more preferably 6.8 or greater, and even more preferably 6.9 or greater, from the viewpoint of adjusting the zeta potential of the silica particles to a negative value and the zeta potential of the silicon substrate to be polished to a positive value, and from the viewpoint of improving the polishing rate, and from the similar viewpoints, is preferably less than 7.7, more preferably 7.5 or less, even more preferably 7.3 or less, and even more preferably 7.1 or less.

[0035] From the viewpoint of adjusting the zeta potential of the silica particles to negative and the zeta potential of the silicon substrate to be polished to positive, and from the viewpoint of improving the polishing rate, it is preferable that component B contains one or more monomer-derived constitutional units selected from allylamine and diallylamine. From the viewpoint of availability, in one or more embodiments, component B is preferably an amino group-containing water-soluble polymer containing a constitutional unit derived from allylamine (hereinafter also referred to as "component B1"), and in one or more embodiments, it is preferably an amino group-containing water-soluble polymer containing a constitutional unit derived from diallylamine (hereinafter also referred to as "component B2").

[0036] (Component B1: Amino group-containing water-soluble polymer containing structural units derived from allylamine) In one or more embodiments, at least a part of the amino groups in the allylamine-derived structural unit preferably has a steric shielding group from the viewpoint of adjusting the zeta potential of the silica particles to a negative value and the zeta potential of the polished silicon substrate to a positive value and from the viewpoint of improving the polishing rate. In the present disclosure, the steric shielding group refers to a three-dimensional (bulky) substituent that can shield the nitrogen atom of the amino group of component B to suppress cationization, that is, to lower the pKa. From the same viewpoint, the amino group having the steric shielding group is preferably a secondary amino group or a tertiary amino group containing a hydrocarbon group having 3 to 11 carbon atoms and having a hydroxyl group. The number of carbon atoms of the hydrocarbon group is preferably 3 or more from the viewpoint of improving the shielding property of the amino group (suppressing the cationization of the nitrogen atom of the amino group) and from the viewpoint of improving the polishing rate, and from the viewpoint of improving water solubility and availability, it is preferably 11 or less, more preferably 7 or less, even more preferably 5 or less, and even more preferably 4 or less.

[0037] In one or more embodiments, the amino group having a steric shielding group is a modified group of an amino group by a glycidol derivative, and in one or more embodiments, it is a group formed by reacting an amino group in an allylamine-derived structural unit with a glycidol derivative. At least a part of the amino groups of component B1 are modified by a glycidol derivative to become an amino group having a steric shielding group. The equivalent of the glycidol derivative to the number of amino groups (1 equivalent) in the allylamine-derived structural unit (hereinafter also referred to as "glycidol modification rate") is preferably more than 1.1, more preferably 1.2 or more, even more preferably 1.3 or more, even more preferably 1.4 or more, and from the same viewpoint, it is preferably less than 1.7, and more preferably 1.6 or less.

[0038] In the present disclosure, the glycidol modification rate is 13 The glycidol modification rate is a value measured by the method described in the Examples using C-NMR, however, the glycidol modification rate can also be measured by the following method (1) or (2). (1) It can be calculated from the amino group equivalent of the allylamine polymer and the number of moles of the glycidol derivative used as the reaction raw material. (2) The nitrogen content N (mass%) of the reaction product of a glycidol derivative and an allylamine polymer is measured, and the nitrogen content N can be calculated from the following formula. Glycidol modification rate = A / B Here, A=(100-N×molecular weight of allylamine monomer / 14) / molecular weight of glycidol derivative, and B=N / 14.

[0039] Examples of the glycidol derivative include glycidol and alkyl glycidyl ether, and glycidol is preferred from the viewpoint of availability and improving the polishing rate. The alkyl group of the alkyl glycidyl ether is preferably an alkyl group having 1 to 8 carbon atoms from the viewpoint of availability, and examples of the alkyl glycidyl ether include methyl, ethyl, propyl, butyl, and 2-ethylhexyl groups. Examples of the alkyl glycidyl ether include methyl glycidyl ether and 2-ethylhexyl glycidyl ether.

[0040] In one or more embodiments, component B1 may be a polyallylamine in which at least a part of the amino groups has a steric shielding group, from the viewpoint of availability and improvement of the polishing rate, and in one or more embodiments, a reaction product of polyallylamine and a glycidol derivative may be used. In terms of adjusting the zeta potential of the silica particles to a negative value and the zeta potential of the silicon substrate to be polished to a positive value, from the viewpoint of improving the polishing rate, and from the viewpoint of availability, component B1 is preferably a reaction product of polyallylamine and a glycidol derivative, and the equivalent of the glycidol derivative relative to the number of amino groups (1 equivalent) of polyallylamine is more than 1.1 and less than 1.7.

[0041] In one or more embodiments, an example of Component B1 is a compound containing a structural unit represented by the following formula (I) (glycidol-modified polyallylamine). [ka]

[0042] In formula (I), R 1 and R 2 are each a hydrogen atom or a sterically shielding group. Examples of the sterically shielding group include a modification group derived from a glycidol derivative, and in one or more embodiments, a 1-mol adduct or 2-mol adduct of glycidol is included. In one or more embodiments, -CH 2 CH(OH)CH 2 (OH), -CH 2 CH(OH)CH2 O-CH 2 CH(OH)CH 2 (OH) and the like.

[0043] (Component B2: Amino group-containing water-soluble polymer containing a constitutional unit derived from diallylamine) In one or more embodiments, at least a part of the amino groups in the diallylamine-derived constitutional unit preferably has an electron-withdrawing group at the β- or γ-position of the amino group, from the viewpoint of adjusting the zeta potential of the silica particles to a negative value and the zeta potential of the silicon substrate to be polished to a positive value, and from the viewpoint of improving the polishing rate. Examples of the electron-withdrawing group include a group represented by the following formula (II).

[0044] [ka]

[0045] In one or more embodiments, component B2 includes a compound containing a diallylamine-derived constituent unit and a sulfur dioxide-derived constituent unit, for example, a compound containing a constituent unit represented by the following formula (III). [ka]

[0046] In formula (III), R 3 is an alkyl group having 1 to 3 carbon atoms which may have a hydroxyl group. From the viewpoint of availability and economic efficiency, R 3 is preferably a methyl group. Also, n+m=1, and n and m are 0 or 1. From the same viewpoint, a compound where m=1 and n=0 is preferred. A mixture of a compound where m=1 and n=0 and a compound where m=0 and n=1 may also be used.

[0047] In one or more embodiments, Component B2 includes a compound containing a constituent unit represented by the following formula (IV), such as a methyldiallylamine / sulfur dioxide copolymer. [ka]

[0048] The weight average molecular weight of component B is preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, and even more preferably 2,000 or more from the viewpoint of improving the polishing rate by making the zeta potential of the polished silicon substrate positive, and from the viewpoint of improving the polishing rate by making the zeta potential of the silica particles negative, from the viewpoint of storage stability, and from the viewpoint of reducing surface roughness and surface defects, it is preferably 100,000 or less, more preferably 50,000 or less, even more preferably 30,000 or less, even more preferably 20,000 or less, even more preferably 15,000 or less, and even more preferably 12,000 or less. The weight average molecular weight of component B in the present disclosure can be measured, for example, by the method described in the Examples.

[0049] When component B is component B1, the weight average molecular weight of component B is, from the viewpoint of making the zeta potential of the silicon substrate to be polished positive and improving the polishing rate, preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, even more preferably 2,000 or more, preferably 3,000 or more, more preferably 5,000 or more, and even more preferably 7,000 or more; and from the viewpoint of making the zeta potential of the silica particles negative and improving the polishing rate, from the viewpoint of storage stability, and from the viewpoint of reducing surface roughness and surface defects, it is preferably 100,000 or less, more preferably 50,000 or less, even more preferably 30,000 or less, even more preferably 20,000 or less, even more preferably 15,000 or less, even more preferably 12,000 or less, and even more preferably 10,000 or less.

[0050] When component B is component B2, the weight average molecular weight of component B is preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, and even more preferably 2,000 or more, from the viewpoint of making the zeta potential of the silicon substrate to be polished positive and improving the polishing rate, and from the viewpoint of making the zeta potential of the silica particles negative and improving the polishing rate, from the viewpoint of storage stability, and from the viewpoint of reducing surface roughness and surface defects, it is preferably 100,000 or less, more preferably 50,000 or less, even more preferably 30,000 or less, even more preferably 20,000 or less, even more preferably 15,000 or less, even more preferably 12,000 or less, even more preferably 10,000 or less, even more preferably 7,000 or less, even more preferably 5,000 or less, and even more preferably 4,000 or less.

[0051] The content of component B in the polishing liquid composition of the present disclosure is preferably 10 mass ppm or more, more preferably 20 mass ppm or more, and even more preferably 30 mass ppm or more from the viewpoint of making the zeta potential of the silicon substrate to be polished positive and improving the polishing rate, and is preferably 200 mass ppm or less, more preferably 150 mass ppm or less, and even more preferably 120 mass ppm or less from the viewpoint of making the zeta potential of the silica particles negative and improving the polishing rate. In the present disclosure, 1 mass% is 10,000 mass ppm (the same applies below).

[0052] The ratio of the content of component B to the content of component A in the polishing liquid composition of the present disclosure (mass ratio B / A) is preferably 0.008 or more, more preferably 0.016 or more, and even more preferably 0.025 or more, from the viewpoint of making the zeta potential of the silicon substrate to be polished positive and thereby improving the polishing rate, and is preferably 0.16 or less, more preferably 0.12 or less, and even more preferably 0.09 or less, from the viewpoint of making the zeta potential of the silica particles negative and thereby improving the polishing rate.

[0053] [water] In one or more embodiments, the polishing liquid composition of the present disclosure may contain water. Examples of water include ion-exchanged water and ultrapure water. The content of water in the polishing liquid composition of the present disclosure may be, for example, the remainder of component A, component B, and any optional components described below.

[0054] [Nitrogen-containing basic compound (component C)] In one or more embodiments, the polishing liquid composition of the present disclosure preferably further contains a nitrogen-containing basic compound (hereinafter also referred to as "component C") from the viewpoint of adjusting the pH. Component C is preferably a water-soluble nitrogen-containing basic compound from the viewpoint of achieving both improved polishing rate and storage stability, and from the viewpoint of improving surface quality. In the present disclosure, "water-soluble" refers to having a solubility of 0.5 g / 100 mL or more, preferably 2 g / 100 mL or more, in water (20°C). In the present disclosure, "water-soluble nitrogen-containing basic" refers to a nitrogen-containing compound that exhibits basicity when dissolved in water. In one or more embodiments, component C does not include an amino group-containing water-soluble polymer (component B). Component C may be one type or a combination of two or more types.

[0055] In one or more embodiments, component C may be at least one selected from an amine compound and an ammonium compound. For example, component C may be one or a combination of two or more selected from ammonia, ammonium hydroxide, ammonium carbonate, ammonium hydrogen carbonate, dimethylamine, trimethylamine, diethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, N-methylethanolamine, N-methyl-N,N-diethanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, N,N-dibutylethanolamine, N-(β-aminoethyl)ethanolamine, monoisopropanolamine, diisopropanolamine, triisopropanolamine, ethylenediamine, hexamethylenediamine, piperazine hexahydrate, anhydrous piperazine, 1-(2-aminoethyl)piperazine, N-methylpiperazine, diethylenetriamine, tetramethylammonium hydroxide, and hydroxylamine. Among these, from the viewpoint of achieving both an improvement in the removal rate and storage stability, Component C is preferably ammonia or a mixture of ammonia and hydroxyamine, and more preferably ammonia.

[0056] When the polishing liquid composition of the present disclosure contains component C, the content of component C in the polishing liquid composition of the present disclosure is preferably 5 mass ppm or more, more preferably 10 mass ppm or more, and even more preferably 20 mass ppm or more from the viewpoint of improving the polishing rate, and is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, and even more preferably 150 mass ppm or less from the viewpoint of improving storage stability, improving surface quality, and suppressing corrosion of silicon substrate. From the same viewpoint, the content of component C in the polishing liquid composition of the present disclosure is preferably 5 mass ppm or more and 500 mass ppm or less, more preferably 10 mass ppm or more and 300 mass ppm or less, and even more preferably 20 mass ppm or more and 150 mass ppm or less. When component C is a combination of two or more kinds, the content of component C refers to their total content.

[0057] When the polishing liquid composition of the present disclosure contains component C, the ratio C / A (mass ratio C / A) of the content of component C to the content of component A in the polishing liquid composition of the present disclosure is preferably 0.002 or more, more preferably 0.01 or more, and even more preferably 0.015 or more from the viewpoint of improving the polishing rate, and is preferably 1 or less, more preferably 0.5 or less, even more preferably 0.1 or less, and even more preferably 0.05 or less from the viewpoint of improving storage stability, improving surface quality, and suppressing corrosion of the silicon substrate. From the same viewpoint, the mass ratio C / A in the polishing liquid composition of the present disclosure is preferably 0.002 or more and 1 or less, more preferably 0.01 or more and 0.5 or less, even more preferably 0.01 or more and 0.1 or less, and even more preferably 0.015 or more and 0.05 or less.

[0058] [Other ingredients] The polishing liquid composition of the present disclosure may further contain other components within the range of making the zeta potential of the silica particles negative and the zeta potential of the silicon substrate to be polished positive. In one or more embodiments, the other components include water-soluble polymers other than component B, pH adjusters other than component C, preservatives, alcohols, chelating agents, and oxidizing agents.

[0059] [pH] The pH of the polishing liquid composition of the present disclosure is preferably more than 8.5, more preferably 9 or more, even more preferably 9.5 or more, and even more preferably 10 or more, from the viewpoint of improving the polishing rate and storage stability, and is preferably 14 or less, more preferably 13 or less, even more preferably 12.5 or less, even more preferably 12 or less, even more preferably 11.5 or less, and even more preferably 11 or less. From the same viewpoint, the pH of the polishing liquid composition of the present disclosure is preferably more than 8.5 to 14 or less, more preferably 9 to 13 or less, even more preferably 9.5 to 12.5 or less, even more preferably 9.5 to 12 or less, even more preferably 9.5 to 11.5 or less, and even more preferably 10 to 11 or less. The pH of the polishing liquid composition of the present disclosure can be adjusted using component C or a known pH adjuster. In the present disclosure, the above pH is a value measured by the method described in the Examples.

[0060] [pH-pKa] From the viewpoints of improving the polishing rate and improving storage stability, the pH of the polishing liquid composition of the present disclosure is preferably higher than the pKa of component B. From the same viewpoints, the difference between the pH and the pKa (pH-pKa) is preferably more than 0.8, more preferably 1 or more, even more preferably 2 or more, and even more preferably 2.5 or more, and from the viewpoint of improving the surface quality, it is preferably 6.3 or less, more preferably 5 or less, even more preferably 4.5 or less, even more preferably 4 or less, and even more preferably 3.5 or less.

[0061] The polishing liquid composition of the present disclosure can be produced, for example, by blending component A and component B, and, if desired, water, component C, and other components by a known method. That is, the polishing liquid composition of the present disclosure can be produced, for example, by blending at least component A and component B. Therefore, in another aspect, the present disclosure relates to a method for producing a polishing liquid composition, which includes a step of blending at least component A and component B. In the present disclosure, "blending" includes mixing component A, component B, and, if necessary, water, component C, and other components simultaneously or in any order. The blending can be performed using, for example, a stirrer such as a homomixer, a homogenizer, an ultrasonic disperser, a wet ball mill, or a bead mill. The preferred blending amount of each component in the method for producing a polishing liquid composition of the present disclosure can be the same as the preferred content of each component in the polishing liquid composition of the present disclosure described above.

[0062] In the present disclosure, "the content of each component in the polishing liquid composition" refers to the content of each component at the time of use, that is, at the time when the polishing liquid composition is started to be used for polishing.

[0063] The polishing liquid composition of the present disclosure may be produced as a concentrate from the viewpoint of storage and transportation, and diluted at the time of use. The dilution ratio is preferably 2 times or more, more preferably 10 times or more, even more preferably 30 times or more, and even more preferably 50 times or more from the viewpoint of production and transportation costs, and is preferably 180 times or less, more preferably 140 times or less, even more preferably 100 times or less, and even more preferably 70 times or less from the viewpoint of storage stability. The polishing liquid composition concentrate of the present disclosure can be used by diluting with water so that the content of each component at the time of use is the above-mentioned content (i.e., the content at the time of use). In the present disclosure, the "time of use" of the polishing liquid composition concentrate refers to the state in which the polishing liquid composition concentrate is diluted.

[0064] [Method of manufacturing semiconductor substrate] In another aspect, the present disclosure relates to a method for manufacturing a semiconductor substrate (hereinafter also referred to as the "semiconductor substrate manufacturing method of the present disclosure"), which includes a step of polishing a silicon substrate to be polished using the polishing method of the present disclosure (hereinafter also referred to as the "polishing step") and a step of cleaning the polished silicon substrate (hereinafter also referred to as the "cleaning step"). According to the semiconductor substrate manufacturing method of the present disclosure, the polishing rate can be improved by using the polishing method of the present disclosure, so that high-quality semiconductor substrates can be manufactured at high yield, high productivity, and low cost.

[0065] The polishing step in the semiconductor substrate manufacturing method of the present disclosure can include, for example, a lapping (rough polishing) step of planarizing a single crystal silicon substrate obtained by slicing a single crystal silicon ingot into a thin disk shape, and a finish polishing step of mirror-finishing the surface of the single crystal silicon substrate after etching the lapped single crystal silicon substrate. The polishing liquid composition of the present disclosure is more preferably used in the finish polishing step from the viewpoint of achieving both an improvement in the polishing rate and an improvement in the surface quality.

[0066] The polishing step in the semiconductor substrate manufacturing method of the present disclosure can include, for example, a step of removing irregularities in the polysilicon film to planarize a substrate in which a polysilicon film is formed by chemical vapor deposition (CVD) on a silicon substrate having a silicon dioxide film and a silicon nitride film, and a step of simultaneously polishing and planarizing the silicon dioxide film and silicon nitride film directly below and the polysilicon film. From the viewpoint of achieving both an improvement in the polishing rate and an improvement in the surface quality, the polishing liquid composition of the present disclosure is more preferably used in the step of removing irregularities in the polysilicon film to planarize the substrate.

[0067] In the polishing step in the semiconductor substrate manufacturing method of the present disclosure, polishing can be performed under the same conditions (zeta potential of the silica particles and the silicon substrate to be polished, polishing pressure, polishing liquid composition and surface temperature of the polishing pad, etc.) as in the polishing step in the polishing method of the present disclosure described above.

[0068] In one or more embodiments, the method for producing a semiconductor substrate according to the present disclosure may include a dilution step of diluting a concentrate of the polishing liquid composition according to the present disclosure prior to the polishing step. The dilution medium may be, for example, water.

[0069] In the cleaning step in the semiconductor substrate manufacturing method of the present disclosure, it is preferable to perform inorganic cleaning from the viewpoint of reducing residues on the silicon substrate surface. Examples of the cleaning agent used in inorganic cleaning include inorganic cleaning agents containing at least one selected from hydrogen peroxide, ammonia, hydrochloric acid, sulfuric acid, hydrofluoric acid, and ozone water.

[0070] In one or a plurality of embodiments, the semiconductor substrate manufacturing method of the present disclosure can further include, after the cleaning step, a step of rinsing the cleaned silicon substrate with water and drying it. EXAMPLES

[0071] The present disclosure will be described in more detail below with reference to examples, but these are merely illustrative and the present disclosure is not limited to these examples.

[0072] 1. Preparation of polishing composition (Polishing composition concentrate) A concentrate (60 times) of the polishing liquid composition was obtained by mixing and stirring the silica particles (component A) shown in Tables 1 and 2, the water-soluble polymer (component B or non-component B) shown in Tables 1 and 2, ammonia (component C), and ultrapure water. The pH of the concentrate at 25°C was 10.6 to 11.0. (polishing liquid composition) The concentrate was diluted 60 times with ion-exchanged water to obtain polishing liquid compositions of Examples 1 to 4 and Comparative Examples 1 to 4. The content of each component in Tables 1 and 2 is the content of each component (mass % or mass ppm, active content) at the time of use of the diluted polishing liquid composition. The content of ultrapure water is the remainder excluding component A and component B or non-component B and component C. The pH of each polishing liquid composition (at the time of use) at 25°C was 10.3. The pH at 25° C. was measured using a pH meter (Toa Denpa Kogyo Co., Ltd., HM-30G), and was the value measured one minute after immersing the electrodes of the pH meter in the polishing composition or a concentrate thereof.

[0073] The following components A, B, non-component B, and C were used in the preparation of each polishing composition. (Component A) Colloidal silica [average primary particle size 25 nm, average secondary particle size 49 nm, degree of association 2.0] (Component B) Methyldiallylamine-sulfur dioxide copolymer [Nittobo Medical Co., Ltd., PAS-2201, weight average molecular weight 3,000] Glycidol-modified polyallylamine (glycidol modification ratio: 1.5) [Nittobo Medical Co., Ltd., weight average molecular weight 8,900] (Non-ingredient B) Polyglycerin [Daicel's "XPW", polymerization degree 40, weight average molecular weight 2,980] Dimethyldiallylammonium chloride-sulfur dioxide copolymer [Nittobo Medical Co., Ltd., PAS-A-5, weight average molecular weight 5,000] (Component C) Ammonia [28% by weight ammonia water, Kishida Chemical Co., Ltd., special grade reagent]

[0074] 2.Measuring methods for various parameters (1) Measurement of the average primary particle size of silica particles (component A) The average primary particle size (nm) of component A is calculated by the BET (nitrogen adsorption) method. 2 / g) using the following formula: Average primary particle diameter (nm)=2727 / S

[0075] The specific surface area S of component A was measured by carrying out the following [pretreatment], and then weighing out approximately 0.1 g of the measurement sample into a measurement cell to four decimal places, drying the sample for 30 minutes in an atmosphere at 110°C immediately before measuring the specific surface area, and then measuring the specific surface area by the nitrogen adsorption method (BET method) using a specific surface area measuring device (Micromeritic automatic specific surface area measuring device "Flowsorb III2305", manufactured by Shimadzu Corporation). [Preprocessing] (a) The pH of the slurry of component A is adjusted to 2.5±0.1 with an aqueous solution of nitric acid. (b) The slurry of component A, adjusted to pH 2.5±0.1, is placed in a petri dish and dried in a hot air dryer at 150°C for 1 hour. (c) After drying, the obtained sample is finely ground in an agate mortar. (d) The ground sample is suspended in ion-exchanged water at 40°C and filtered through a membrane filter with a pore size of 1 μm. (e) The residue on the filter is washed five times with 20 g of ion-exchanged water (40°C). (f) The filter with the filtrate attached thereto is placed in a petri dish and dried in an atmosphere at 110°C for 4 hours. (g) The dried filtrate (component A) was taken, being careful not to mix in any filter debris, and finely ground in a mortar to obtain a measurement sample.

[0076] (2) Average secondary particle size of silica particles (component A) The average secondary particle diameter (nm) of component A was measured by adding an abrasive to ion-exchanged water so that the concentration of component A was 0.25 mass%, and then placing the resulting aqueous dispersion in a disposable sizing cuvette (a 10 mm polystyrene cell) to a height of 10 mm from the bottom, and using a dynamic light scattering method (apparatus name: Zetasizer Nano ZS, manufactured by Sysmex Corporation).

[0077] (3) Measurement of weight-average molecular weight of water-soluble polymers The weight average molecular weight of the water-soluble polymers (component B, non-component B) was calculated based on peaks in a chromatogram obtained by applying gel permeation chromatography (GPC) under the following conditions. <Polyglycerin (non-ingredient B)> Equipment: HLC-8320 GPC (Tosoh Corporation, detector integrated) Column: GMPWXL+GMPWXL (anion) Eluent: 0.2M phosphate buffer / CH 3 CN=9 / 1 Flow rate: 0.5mL / min Column temperature: 40℃ Detector: Shodex RI SE-61 differential refractive index detector Standard: Monodisperse polyethylene glycol with known molecular weight <Amino group-containing water-soluble polymer (component B), ammonium salt-containing water-soluble polymer (non-component B)> Equipment: HLC-8320 GPC (Tosoh Corporation, detector integrated) Column: GS-220HQ+GS-620HQ Eluent: 0.4M NaCl Flow rate: 1.0mL / min Column temperature: 30℃ Detector: Shodex RI SE-61 differential refractive index detector Standard: Monodisperse polyethylene glycol with known molecular weight

[0078] (4) pKa measurement Using a HM-41K pH meter (Toa DKK Co., Ltd.), an aqueous solution of component B adjusted to 1 M was subjected to potentiometric titration at room temperature with 0.1 M hydrochloric acid. The pKa was calculated from the obtained titration curve.

[0079] (5) Glycidol modification rate The glycidol modification rate is 13 The carbon-carbon NMR spectroscopy was used to determine the <Measurement conditions> Sample: 200 mg of glycidol-modified polyallylamine dissolved in 0.6 mL of heavy water Equipment used: 400MHz 13 C-NMR (Agilent Technologies, Inc. "Agilent 400-MR DD2") Measurement conditions: 13 C-NMR measurement, pulse interval time 5 seconds, tetramethylsilane as standard peak (σ: 0.0 ppm) Accumulation count: 5000 times Each peak range used for integration: A: 71.0 to 72.3 ppm (integral value of the peak of C bound to the secondary hydroxyl group of glycidol reacted with amino group) B: 32.0 to 41.0 ppm (integrated value of the peak of the main chain C of allylamine) <Glycidol modification rate> The glycidol modification rate (ratio of glycidol equivalents to amino group equivalents) is calculated using the following formula. Glycidol modification rate (equivalent ratio) = 2A / B

[0080] 3. Evaluation of the polishing compositions of Examples 1 and 2 and Comparative Examples 1 and 2 (1) Measurement of the zeta potential of silica particles and polished silicon substrates Each of the aqueous dispersions shown below was placed in a capillary cell DTS1070, and the zeta potential was measured under the following conditions using a Zetasizer Nano ZS (manufactured by Malvern). Sample: Refractive index: 1.450 Absorption coefficient: 0.010 Dispersion medium: Viscosity: 0.8872cP, Refractive index: 1.330, Dielectric constant: 78.5 Temperature: 25℃ (1-1) Preparation of aqueous dispersion for measuring zeta potential of silica particles The polishing liquid compositions (as used) of Examples 1 and 2 and Comparative Examples 1 and 2 were used as they were as aqueous dispersions for measuring the zeta potential of silica particles. (1-2) Preparation of aqueous dispersion for measuring the zeta potential of single crystal silicon substrate The water-soluble polymer and the ammonia aqueous solution described in each of Examples 1 and 2 and Comparative Examples 1 and 2 were added to ion-exchanged water, and then 0.1 mass % of fine particles of single crystal silicon substrate ground in a bead mill was added, and the mixture was filtered with a syringe filter (manufactured by Sartorius, pore size 1.2 μm) to obtain an aqueous dispersion for measuring the zeta potential of the single crystal silicon substrate.

[0081] (2) Polishing method etc. Each polishing composition was filtered with a filter (compact cartridge filter "MCP-LX-C10S", manufactured by Advantech Co., Ltd.) immediately before polishing, and finish polishing and cleaning were performed on the following silicon substrates under the following polishing conditions. <Silicon substrate to be polished> Single crystal silicon substrate [single-sided mirror-finished silicon substrate with a diameter of 200 mm, conductivity type: P, crystal orientation: 100, resistivity: 0.1 Ω·cm or more but less than 100 Ω·cm] The single crystal silicon substrate was previously subjected to rough polishing using a commercially available polishing composition (GLANZOX 1302, manufactured by Fujimi Inc.). After rough polishing, the single crystal silicon substrate was subjected to finish polishing, and had a haze of 2 to 3 ppm.

[0082] <Finish polishing conditions> Polishing machine: Single-sided 8-inch polishing machine "GRIND-X SPP600s" (manufactured by Okamoto Kogyo) Polishing pad: Suede pad (manufactured by Toray Co., Ltd., Asker hardness: 64, thickness: 1.37 mm, nap length: 450 μm, opening diameter: 60 μm) Silicon substrate polishing pressure: 100g / cm 2 Plate rotation speed: 60 rpm Polishing time: 5 minutes Supply rate of polishing composition: 150 g / min Temperature of the polishing composition: 23°C Carrier rotation speed: 62 rpm

[0083] <Measurement of surface roughness (haze) of silicon substrate> The value (DWO haze) measured in a dark field wide oblique incidence channel (DWO) using a surface roughness measuring device "Surfscan SP1-DLS" (KLA Tencor) was used.

[0084] <Cleaning method> After the finish polishing, the silicon substrate was subjected to ozone cleaning and dilute hydrofluoric acid cleaning as described below. In the ozone cleaning, an aqueous solution containing 20 ppm ozone was sprayed from a nozzle at a flow rate of 1 L / min toward the center of the silicon substrate rotating at 600 rpm for 3 minutes. The temperature of the ozone water was kept at room temperature. Next, dilute hydrofluoric acid cleaning was performed. In the dilute hydrofluoric acid cleaning, an aqueous solution containing 0.5 mass% ammonium hydrogen fluoride (special grade, Nacalai Tesque, Inc.) was sprayed from a nozzle at a flow rate of 1 L / min toward the center of the silicon substrate rotating at 600 rpm for 6 seconds. The above ozone cleaning and dilute hydrofluoric acid cleaning were performed as one set, for a total of two sets, and finally spin drying was performed. In the spin drying, the silicon substrate was rotated at 1,500 rpm.

[0085] (3) Evaluation of polishing speed The weight of each silicon substrate before and after polishing was measured using a precision balance ("BP-210S" manufactured by Sartorius), and the weight difference obtained was divided by the density, area and polishing time of the silicon substrate to obtain the single-sided polishing rate per unit time. The results are shown in Table 1. The weight of the silicon substrate after polishing refers to the weight of the silicon substrate after the above-mentioned finish polishing and cleaning were performed.

[0086] [Table 1]

[0087] As shown in Table 1, the polishing liquid compositions of Examples 1 and 2, in which polishing was performed under conditions where the zeta potential of component A was negative and the zeta potential of the silicon substrate to be polished was positive, were found to have a superior removal rate compared to the polishing liquid compositions of Comparative Examples 1 and 2, in which polishing was performed under conditions where the zeta potentials of component A and the silicon substrate to be polished were both negative or both positive (conditions where the zeta potentials had the same sign).

[0088] 4. Evaluation of the polishing compositions of Examples 3 and 4 and Comparative Examples 3 and 4 (1) Measurement of the zeta potential of silica particles and polished silicon substrates The zeta potentials of the silica particles and the silicon substrate to be polished were evaluated in the same manner as in 3(1) above using the following aqueous dispersions. The results are shown in Table 2. (1-1) Preparation of aqueous dispersion for measuring zeta potential of silica particles The polishing liquid compositions (as used) of each of Examples 3 to 4 and Comparative Examples 3 to 4 were used as they were as aqueous dispersions for measuring the zeta potential of silicon particles. (1-2) Preparation of aqueous dispersion for measuring zeta potential of polysilicon substrate The water-soluble polymer and the ammonia solution described in each of Examples 3 to 4 and Comparative Examples 3 to 4 were added to ion-exchanged water, and then 0.1 mass % of fine particles of polysilicon (polycrystalline) substrate ground in a bead mill was added, and the mixture was filtered through a syringe filter (manufactured by Sartorius, pore size 1.2 μm) to obtain an aqueous dispersion for measuring the zeta potential of the polysilicon substrate.

[0089] (2) Polishing method Each polishing composition was filtered using a filter (compact cartridge filter "MCP-LX-C10S", manufactured by Advantech Co., Ltd.) immediately before polishing, and the following silicon substrates were polished under the same polishing conditions as in 3(2) above, and then cleaned using the same cleaning method as in 3(2) above. <Silicon substrate to be polished> A polysilicon substrate [a 200 mm diameter silicon single-sided mirror substrate (conductivity type: P, crystal orientation: 100, resistivity: 0.1 Ω cm or more, but less than 100 Ω cm)] was deposited on the substrate by plasma CVD. 2A 4400 Å thick silicon film was then deposited on the substrate by plasma CVD.

[0090] (3) Evaluation of polishing speed The polishing rate was evaluated using a polysilicon substrate as the silicon substrate to be polished in the same manner as in 3(3) above. The results are shown in Table 2.

[0091] [Table 2]

[0092] As shown in Table 2, the polishing liquid compositions of Examples 3 and 4, in which polishing was performed under conditions where the zeta potential of component A was negative and the zeta potential of the silicon substrate to be polished was positive, were found to have a superior removal rate compared to the polishing liquid compositions of Comparative Examples 3 and 4, in which polishing was performed under conditions where the zeta potentials of component A and the silicon substrate to be polished were both negative or both positive (conditions where the zeta potentials had the same sign). [Industrial Applicability]

[0093] The polishing method of the present disclosure can improve the polishing rate, and is therefore useful as a polishing method used in the manufacturing process of various semiconductor substrates, and is particularly useful as a finish polishing method for silicon substrates.

Claims

1. The method includes a step of polishing a silicon substrate using a polishing composition containing silica particles (component A) and an amino group-containing water-soluble polymer (component B), The pH of the polishing composition is more than 8.5 and not more than 14, The polishing method is carried out under the condition that the zeta potential of component A is negative and the zeta potential of the silicon substrate to be polished is positive.

2. 2. The polishing method according to claim 1, wherein the zeta potential of component A is −50 mV or more and less than 0 mV.

3. 3. The polishing method according to claim 1, wherein the silicon substrate to be polished has a zeta potential of more than 0 mV and not more than 30 mV.

4. The polishing method according to claim 1 , wherein the pKa of component B is greater than 6.7 and less than 7.

7.

5. The polishing method according to claim 1 , wherein the pH of the polishing composition is higher than the pKa of component B.

6. The polishing method according to claim 1 , wherein the content of Component A in the polishing composition is 0.01 mass % or more and 2.5 mass % or less.

7. The polishing method according to claim 1 , wherein the content of Component B in the polishing composition is 10 ppm by mass or more and 200 ppm by mass or less.

8. 8. The polishing method according to claim 1, wherein the ratio B / A of the content of component B to the content of component A in the polishing composition is 0.008 or more and 0.16 or less.

9. 9. The polishing method according to claim 1, wherein Component B contains a constituent unit derived from one or more monomers selected from allylamine and diallylamine.

10. The polishing method according to claim 9 , wherein at least a portion of the amino groups in the constitutional units derived from allylamine have a sterically shielding group.

11. 11. The polishing method according to claim 9, wherein at least a part of the amino groups in the structural unit derived from allylamine is a secondary amino group or a tertiary amino group containing a hydrocarbon group having 3 to 11 carbon atoms and a hydroxyl group.

12. 12. The polishing method according to claim 1, wherein component B is a reaction product of polyallylamine and a glycidol derivative, and the equivalent of the glycidol derivative relative to the number of amino groups (1 equivalent) of the polyallylamine is more than 1.1 and less than 1.

7.

13. The polishing method according to claim 12, wherein the glycidol derivative is glycidol.

14. 10. The polishing method according to claim 9, wherein at least a portion of the amino groups in the constitutional units derived from diallylamine have an electron-withdrawing group at the β-position or the γ-position.

15. 15. The polishing method according to claim 1, wherein Component B is a compound containing a structural unit represented by the following formula (III): 【Chemistry 1】 In formula (III), R 3 represents an alkyl group having 1 to 3 carbon atoms which may have a hydroxyl group, and n+m=1.

16. A step of polishing a silicon substrate to be polished using the polishing method according to any one of claims 1 to 15; and cleaning the polished silicon substrate.

Citation Information

Patent Citations

  • Polishing fluid composition

    JP2002201462A

  • Grinding composition and silicon wafer grinding method employing the same, as well as rinsing composition and silicon wafer rinsing method employing the same

    JP2004128089A

  • Polishing liquid composition

    JP2005262413A

  • Anionic abrasive particles treated with positively charged polyelectrolytes for cmp

    JP2005518091A

  • Composition for polishing semiconductor

    JP2007019093A